Torsion of the vermiform appendix in a 11-year-old boy: A case report - Takwa Mili; Yosra Ben Ahmed; Walid Cherifi; Wiem Douira; Said Jlidi (Journal of Pediatric Surgery Case Reports, 2023)
Introduction: Torsion of the vermiform appendix is a rare disease with symptoms very similar to those of acute appendicitis. We herein report a case of torsion of the vermiform appendix suspected on the preoperative ultrasound and confirmed during the laparotomy. Case presentation: We describe the case of a 11-year-old boy who presented for acute abdominal pain and vomiting and was found to have ultrasound findings suspicious for torsion of the appendiceal base. Laparotomy revealed a 360° clockwise torsion of the vermiform appendix about its base. A routine appendicectomy was performed. Conclusion: Torsion of the vermiform appendix should be considered in the differential diagnosis of acute abdominal pain. Preoperative radiological imaging can be useful in diagnosis.